Chitosan-coated nanoliposomes as vehicles for l-citrulline: Preparation, characterization, antioxidant properties, and nanovesicles behavior - Mahsa Mohseni; Mohammad Mousavi; Hossein Kiani; Mina Homayoonfal (Carbohydrate Polymer Technologies and Applications, 2025)
L-Citrulline is classified as a non-essential amino acid that plays a role in the nitric oxide system in humans. It offers potential antioxidant benefits and may aid in promoting vasodilation. This research aimed to evaluate the stability and bioavailability of uncoated and chitosan-coated nanoliposomes containing l-Citrulline by analyzing such factors as size, morphology, encapsulation efficiency, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and antioxidant activities. The results indicated that both l-Citrulline-loaded nanoliposomes (LP-LC) and l-Citrulline-loaded chitosan-coated nanoliposomes (LP-CH-LC) exhibited a uniform composition, spherical morphology, and small particle sizes. The uncoated nanoliposomes displayed a surface charge of -64.5 mV, while the chitosan-coated nanoliposomes had a positive charge of +62.33 mV, suggesting stability for both nanostructures. Thermal analysis demonstrated enhanced stability for l-Citrulline in both formulations. Shear viscosity measurements indicated a transition in flow characteristics from Newtonian to shear-thinning behavior due to the chitosan coating, which improved mechanical stability. Chitosan coating was hypothesized to enhance performance over conventional encapsulation methods by improving mucosal adhesion, protecting l-Citrulline in acidic gastric environments, and enabling sustained release—all of which contribute to superior bioavailability. This study underscores the potential of both uncoated and chitosan-coated nanoliposomes as effective carriers for bioactive compounds like l-Citrulline, suggesting significant applications in the development of functional products within the food and pharmaceutical sectors.